Plate fixation of periprosthetic femur fractures: What happens to the cement mantle?. (February 2017) - Konstantinidis, Lukas; Schmidt, Benjamin; Bernstein, Anke; Hirschmüller, Anja; Schröter, Steffen; Südkamp, Norbert Paul; Helwig, Peter
Osteosynthesis of periprosthetic femur fractures by screw fixation around the implanted prosthetic stem is currently regarded as the biomechanically superior option compared with cerclage. The aim of this biomechanical study was damage analysis of the cement mantle after revision screw insertion. A prosthetic stem (Bicontact) was implanted in 20 cadaveric femora in cemented technique. A locking compression plate (Synthes) was then applied to the lateral femur at the level of the prosthetic stem. The method of plate fixation to the femur was assigned randomly to three groups: bicortical non-locking screws, monocortical locking screws, and bicortical locking screws. This was followed by applying a fluctuating axial load (2100 N, 0.5 Hz) for 20, 000 cycles. After testing, macroscopic and microscopic evaluations of the cement mantle were conducted. Cracks formed in the cement mantle in 14% of the 80 screw holes. The type of screw (bicortical or monocortical; locking or non-locking) had no significant effect on the number of cracks (p = 0.52). The relationship between manifestation of crack damage and cement mantle thickness was not significant (p = 0.36), whereas the relationship between crack formation and screw position was significant (p = 0.019). Those screws whose circumference was only partially within the cement mantle yielded a significantly lower number of cracks compared with screws positioned completely within the cement mantle or even touching the prosthetic stem. In order to reduce the incidence of crack formation in the cement mantle during plate osteosynthesis of periprosthetic femur fractures, the screws should not be either placed within the cement mantle or make direct contact with the stem.